The relationship of language and culture. Reflection of changes and development of public culture in the language (Texas Journal of Philology, Culture and History, 2023)
The language of any people is its historical memory expressed in words. It is in language and through language that we reveal such most important peculiarities and features as national psychology, people’s character, the way he thinks, his specific ways of creative work, his moral and spiritual state. Consequently, the culture of language can and must be regarded in ecological aspect as an integral part of «speech-environmental existence